An ex-ante evaluation of the impact of COVID-19 on Ecuador’s production network - José Ramírez-Álvarez; Josselyn Ramos; Kevin Gordón (Journal of Economic Structures)
Abstract The COVID-19 pandemic was categorized as a severe global exogenous shock that affected aggregate supply and led to demand distortions. In the present study, we designed an extended Leontief model with foreign trade and gross added value to evaluate the ex-ante effects of the crisis on Ecuador’s production system. The magnitude of the supply and demand shocks caused by the pandemic was compiled through a meta-analysis derived from governmental and non-governmental sources. The results show that the pandemic would generate an average variation in the Gross Domestic Product (GDP) for 2020 of − 7.4%. The most affected sectors would be the manufacture of basic metals, transport equipment, plastic products, and domestic services. In contrast, the most beneficial sectors would be the grain mill products, coffee, bakery, and noodles.